2012
DOI: 10.1096/fj.12-208678
|View full text |Cite
|
Sign up to set email alerts
|

Pain inhibition by blocking leukocytic and neuronal opioid peptidases in peripheral inflamed tissue

Abstract: Inflammatory pain can be controlled by endogenous opioid peptides. Here we blocked the degradation of opioids in peripheral injured tissue to locally augment this physiological system. In rats with hindpaw inflammation, inhibitors of aminopeptidase N (APN; bestatin) or neutral endopeptidase (NEP; thiorphan), and a dual inhibitor, NH(2)-CH-Ph-P(O)(OH)CH(2)-CH-CH(2)Ph(p-Ph)-CONH-CH-CH(3)-COOH (P8B), were applied to injured paws. Combined bestatin (1.25-5 mg)/thiorphan (0.2-0.8 mg) or P8B (0.0625-1 mg) alone elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 57 publications
1
52
0
Order By: Relevance
“…The physiological ligands of MOP and DOP are beta-endorphin, endomorphin-1 and -2 as well as the most abundant pentapeptides Met and Leuenkephalins (Giraud et al, 1983). We decided to test in models of neuropathic pain the efficacy of these latter pentapeptides which are locally released under nocifensive stimuli (Yaksh et al, 1981;Bourgoin et al, 1986;Schreiter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological ligands of MOP and DOP are beta-endorphin, endomorphin-1 and -2 as well as the most abundant pentapeptides Met and Leuenkephalins (Giraud et al, 1983). We decided to test in models of neuropathic pain the efficacy of these latter pentapeptides which are locally released under nocifensive stimuli (Yaksh et al, 1981;Bourgoin et al, 1986;Schreiter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been demonstrated that inhibition of leukocytic and neuronal peptidases in the inflamed paws of rats results in analgesia [17]. However, when the peptidase inhibitors were applied in combination with antibodies against met-enkephalin, leucine-enkephalin and dynorphin 1-17 to the rats paws peripherally, the analgesia was abolished [17].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the concomitant inhibition of both peptidases produces analgesic responses [11,13]. All together, this indicates that increasing enkephalin concentrations at the nociceptor level promotes "physiological analgesia" [6,12], as demonstrated by microdialysis experiments [12e14] and use of antibodies for measurement of enkephalins in injured tissues [15].…”
Section: Introductionmentioning
confidence: 99%